Trends in the prescription of antidiabetic medications from 2009 to 2012 in a general practice of Southern Italy: A population-based study. Issue 1 (April 2015) - Rafaniello, Concetta; Arcoraci, Vincenzo; Ferrajolo, Carmen; Sportiello, Liberata; Sullo, Maria Giuseppa; Giorgianni, Francesco; Trifirò, Gianluca; Tari, Michele; Caputi, Achille P.; Rossi, Francesco; Esposito, Katherine; Giugliano, Dario; et al.
Abstract Objective To assess the prescribing pattern of antidiabetic drugs (AD) in a general practice of Southern Italy from 2009 to 2012, with focus on behaviour prescribing changes. Methods This retrospective, drug utilization study was conducted using administrative databases of the Local Health Unit of Caserta (Southern Italy) including about 1 million citizens. The standardized prevalence of AD use was calculated within each study year. A sample cohort of 78, 789 subjects with at least one prescription of AD was identified during the study period. Results There was an overall increase of the proportion of the patients treated with monotherapy, which was significant for insulin monotherapy (from 11.2 to 14.6%, p < 0.001). The proportion of patients treated with metformin remained stable (from 68.3% to 67.8%, p = 0.076), while those receiving sulfonylurea dropped from 18.4% to 12.5% (p < 0.001); GLP-1 analogues and DPP-4 inhibitors showed the greatest increase (from 1.2% to 6.6%, p < 0.001). In the whole sample of 25, 148 new AD users, metformin was the most commonly prescribed drug in monotherapy (41.9%), while insulin ranked second (13.3%). Conclusion This study shows a rising trend of AD monotherapy, with sulfonylureas and incretins showing the more negative and positive trend, respectively.